Peran Mediator Dalam Mengurangi Tingkat Perceraian di Pengadilan Agama Medan - Wahda Hilwani Damanik; Muthia Erina Nasution; Fauziah Lubis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Article 1 paragraph (1) explains “Mediation is a way of settling disputes through a negotiation processto obtain an agreement between the parties assisted by a mediator”. Paragraph (2) “A mediator is a judge or other party who has a mediator certificates as a neutral party who assists the partes in the negotiation process to find various possibilities for dispute resolution without resorting to deciding or forcing a settlement”. The mediator has carried out mediation to the maximum to increase the success of mediation, especially in divorce cases. Mediation in the Religious Court is a peace process carried out by a mediator judge between the litigants to reach an agreement with a win-win solution. Keywords: Role, Mediator, Divorce, Religious Courts